mTOR-S6K1 pathway mediates cytoophidium assembly - Sun, Z; Liu, J (Elsevier, 2019)
CTP synthase (CTPS), the rate-limiting enzyme in de novo CTP biosynthesis, has been demonstrated to assemble into evolutionarily conserved filamentous structures, termed cytoophidia, in Drosophila, bacteria, yeast and mammalian cells. However, the regulation and function of the cytoophidium remain elusive. Here, we provide evidence that the mechanistic target of rapamycin (mTOR) pathway controls cytoophidium assembly in mammalian and Drosophila cells. In mammalian cells, we find that inhibition of mTOR pathway attenuates cytoophidium formation. Moreover, CTPS cytoophidium assembly appears to be dependent on the mTOR complex 1 (mTORC1) mainly. In addition, knockdown of the mTORC1 downstream target S6K1 can inhibit cytoophidium formation, while overexpression of the constitutively active S6K1 reverses mTOR knockdown-induced cytoophidium disassembly. Finally, reducing mTOR protein expression results in a decrease of the length of cytoophidium in Drosophila follicle cells. Therefore, our study connects CTPS cytoophidium formation with the mTOR signaling pathway.